Restored coastal wetlands with low degree of separation and high patch connectivity attract more birds - Kun He; Kun He; Annan Song; Ziyu Zhang; Naven Ramdat; Jiayi Wang; Wei Wu; Xuechu Chen; Xuechu Chen (Frontiers in Marine Science, 2023)
Coastal wetlands, the major component of coastal ecotones with indispensable ecosystem services, are threatened by anthropogenic disturbance, resulting in continuous loss of ecosystem functions. Coastal wetland restoration can be implemented to deter the ecosystem losses; however, it is unclear whether it could provide appropriate habitat for the birds using on coastal ecotones. Here, we utilize a newly restored wetland as an example to investigate the impacts of coastal restoration on bird diversity, and test the hypothesis - if a reasonable habitat pattern is created, more birds will be attracted, thereby helping decision-makers develop efficient and sustainable coastal restoration strategies. We used Fragstats for landscape pattern analysis, and derived the variability in different habitat patterns by independent sample T-test and Mann-Whitney U test. The results suggested that the restored wetland exhibited a positive effect on attracting birds, with a total of 70 species, 35 families, and 15 orders of birds being recorded over a three-year period after restoration. Passeriformes are the main species, and accounted for 52.8% of bird species. Additionally, waterbird species, i.e., Ciconiiformes and Anseriformes, accounted for 24.67% of the total number of species. The number of bird species in the wetlands increased annually, especially during the overwintering and the breeding period. Furthermore, the results of this study indicate that water-centered mosaic-type habitat consisting of a relatively low degree of separation and high patch connectivity was beneficial to attracting different types of birds. The number of bird species, density, bird biodiversity index, evenness index, and dominance index for mosaic-type habitats were all higher than those for even habitat pattern with independent patches and sharp boundaries. In particular, the mosaic-type habitat attracted migratory waterbirds such as Anas zonorhyncha, Aix galericulata, Mareca penelope, Hydrophasianus chirurgus, Emberiza pallasi, Xenus cinereus, and Spatula querquedula, which expanded the range of birds attracted by coastal restoration projects. This study illustrated that coastal wetland restoration combined with a creation of water-centered mosaic-type habitat attracted more birds and could provide a reference for the restoration of degraded ecosystems in coastal zones.